(untitled) - Chamot, Anna Uhl (Boston, MA., 2002)
Up Close is a four-level course which takes students from the elementary to the intermediates level, by providing clear and achievable goals in each unit and each level of series. It provides a graded, functional, grammatical, and lexical syllabus for students and teachers to work with.
Keywords: English language,Listening; Foreign speakers